RELATIVE STANDING OF ROE AND ROCE IN EFFECTIVE LIQUIDITY MANAGEMENT: EVIDENCE FROM BANGLADESHI COMMERCIAL BANKS - Chaudhury, Nazneen Jahan (American Finance & Banking Review, 2021)
This study has been designed for examining the effectiveness of liquidity management through the relative standing of ROE and ROCE of Nationalized Commercial Banks in Bangladesh for the duration of 2008–2018. Six NCBs are selected purposively as sample. The study relies on a balanced panel data set of 66 observations which are gathered from the annual reports of banks and analyzed by random effects regression model. However, the research only examined a few variables. The empirical results reveal that the selected NCBs have been portraying better standing in case of ROE than ROCE in effective liquidity management. The value of R2 of ROE is 75.25%; it signifies that the explanatory measures could clarify 75.25% of the variations in ROE. Among the liquidity measures, Assets/Shareholders Equity has highly significant negative effect; Tier 1 Capital/Risk Weighted Assets has highly significant positive effect; Deposits/Assets have some significant positive and Bank Size in terms of Deposits has some significant negative effect on ROE of the selected NCBs. JEL Classification Codes: E44, G14, G21, O16.